Investigations on the Growth and Optical, Dielectric and Antibacterial activity of L-Leucine Barium Chloride crystals - Tresa, M; Helina, B.; Vella Durai, S.C. (Eurasian Journal of Physics and Functional Materials, 2026)
In order to create single crystal of L-Leucine Barium Chloride (LLBC), double-distilled water was utilised as solvent in a solution strategy with a lengthy evaporation process. L-Leucine and Barium Chloride, both of which are of AR quality, were bought commercially and consumed in an equal amount. By slow evaporation method single crystals were formed after a period of about 30 days. Solubility tests for the crystal were carried out, and it was observed that solubility increases with temperature. Single crystal X-ray diffraction (XRD) was used to carry out the XRD test to determine the crystal structure of the material and it was found to be orthorhombic. The sample's SHG effectiveness was found using Nd:YAG laser and green laser light was produced by the crystal. A microhardness tester was used to find the mechanical parameters of LLBC crystals, the hardness, work hardening coefficient, yield strength, stiffness constant, resistance pressure, fracture toughness, and brittleness index, have been evaluated to understand the sample's mechanical strength. Following the sample's linear optical exams, numerous linear optical properties of the sample have been computed. The antibacterial activity of four bacterial strains was studied to understand the prevention of the bacterial growth.Recommended CitationTresa, M. Arul; Helina, B.; and Durai, S. C. Vella (2024) "Investigations on the Growth and Optical, Dielectric and Antibacterial activity of L-Leucine Barium Chloride crystals," Eurasian Journal of Physics and Functional Materials: Vol. 8: No. 3, Article 4.DOI: https://doi.org/10.69912/2616-8537.1227